Feasibility of a Self-Managed, Video-Guided Exercise Program for Community-Dwelling People with Stroke - Scrivener, Katharine; Sewastenko, Jessica; Bouvier-Farrell, Alexandra; MacDonald, Katherine; Van Rijn, Tegan; Tezak, Joshua; Mandis, Nicholas; Love, Sherrie (Stroke Research and Treatment, 2021)
Background. Ongoing rehabilitation after stroke is limited. Using video-guided exercises, which are implemented with a self-management approach, may be a way to facilitate ongoing exercise in the home environment. Objectives. To investigate the feasibility of a video-guided exercise program, implemented with a self-management approach for people with stroke. Methods. A phase I, single-group, clinical trial. The study comprised two phases: in phase one, four weeks of the program was supported by weekly supervised sessions and in phase two, four weeks of the program was completed without direct supervision. Demographic information was recorded at baseline. Adherence and adverse events were self-reported via a logbook. Acceptability was measured through a purpose-built scale. Physical performance, physical activity, and exercise self-efficacy were measured at baseline and 4 and 8 weeks. Results. Sixteen people with stroke were recruited; however, 14 commenced and completed the study. Adherence during the supervised phase was 3.3 hours per week and 2.3 hours per week during the self-directed phase. There were no adverse events. Most participants indicated that the program was easy to use (92%) and would recommend the program to others (86%). Walking speed improved over the duration of the program (mean difference -0.12 m/s, 95% CI -0.22 to -0.02, p=0.02). Self-efficacy and physical activity did not change over the duration of the program. Conclusion. The findings support the feasibility of a video-guided exercise program for people with stroke. Further research to confirm the effectiveness of this intervention to improve physical function is warranted.